The merchants of Siberia : trade in early modern Eurasia - Monahan, Erika (Cornell University Press, 2016)
This book reconsiders commerce in early modern Russia by reconstructing the trading world of Siberia and the careers of merchants who traded there. It follows the histories of three merchant families from various social ranks who conducted trade in Siberia for well over a century. These include the Filat'evs, who were among Russia's most illustrious merchant elite; the Shababins, Muslim immigrants who mastered local and long-distance trade while balancing private endeavors with service to the Russian state; and the Noritsyns, traders of more modest status who worked sometimes for themselves, sometimes for bigger merchants, and participated in the emerging Russia-China trade.